2022
DOI: 10.1038/s41598-022-14339-y
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of gold nanoparticles in Gum Arabic using pulsed laser ablation for CT imaging

Abstract: Laser ablation synthesis in liquid solution (PLAL) is a green technique that allows for the physical formation of nanomaterials. This study indicates the preparation of stable gold nanoparticles (AuNPs) in Gum Arabic (GA) solution via laser ablation as a CT contrast agent. The optical properties were achieved using the absorption spectroscopic technique whereas the morphology and size distribution were investigated by TEM and ImageJ software. TEM image shows greater stability and spherical shape of GA-AuNPs wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 58 publications
(73 reference statements)
0
12
0
1
Order By: Relevance
“…When the absorption edges of ZnO nanoparticles get bigger, the optical band gap energy and the amount of light they can pass through go down 21 . In addition, the extrapolation of the hυ versus (αhυ) 2 curve was used to determine the energy band gap for the prepared sample. The optical energy bandgap of the manufactured samples might be ascertained using some techniques, such as the Tauc relation.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…When the absorption edges of ZnO nanoparticles get bigger, the optical band gap energy and the amount of light they can pass through go down 21 . In addition, the extrapolation of the hυ versus (αhυ) 2 curve was used to determine the energy band gap for the prepared sample. The optical energy bandgap of the manufactured samples might be ascertained using some techniques, such as the Tauc relation.…”
Section: Resultsmentioning
confidence: 99%
“…When the NiO NPs are used as shells for ZnO NPs, the optical band gap energy falls from 3.19 eV (pure ZnO) to 2.966 eV. After adding the NiO (shell), the band gap shrank, indicating that the Ni 2 + ions function as defect sites in the valence band to reduce the band gap. The quantum confinement effect can explain the decrease in bandgap energy and the increase in particle size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a study, the results showed that AuNPs could produce sensitization and synergistic effects in radiotherapy using different types of radiation [22][23][24][25]. In a major advance in 2022, Mzwd et al [26] used a green technique for nanoparticle synthesis. They formed and used stable AuNPs in gum arabic (GA) solution via laser ablation technique as a CT contrast agent.…”
Section: Gold-based Nanoparticlesmentioning
confidence: 99%